Production of Crude Xylanase from Thermoascus Aurantiacus CBMAI 756 Aiming the Baking Process - Oliveira, Denise S. [UNESP]; Meherb-Dini, Carolina [UNESP]; Franco, Celia M. L. [UNESP]; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
In recent years, the baking industry has focused its attention on substituting several chemical compounds with enzymes. Enzymes that hydrolyze nonstarch polysaccharides, such as xylanase, lead to the improvement of rheological properties of dough, loaf specific volume, and crumb firmness. The purpose of this study was to find a better solid-state fermentation substrate to produce high levels of xylanase and low levels of protease and amylase, which are enzymes involved in bread quality, from Thermoascus aurantiacus CBMAI 756. Wheat bran, corncob, and corn straw were used as energy sources. The enzyme extract of corncob showed high xylanase activity (130 U/mL) and low amylase and protease activity (< 1 and 15 U/mL, respectively). This enzyme profile may be more profitable for the baking industry, because it results in a slower degradation of gluten. Our results confirm this finding, because the enzyme obtained by fermentation in corncob resulted in a gluten with a higher specific volume than all the other substrates that were tested. The crude xylanase presented maximum activity at a pH of 5, and the optimum temperature was 75 degrees C. It was stable up to 70 degrees C for an hour and at a pH range from 4 to 10.
Keywords: Amylase; baking process; Protease; Solid state fermentation (SSF); Thermoascus aurantiacus; Xylanase